2020
DOI: 10.1371/journal.pmed.1003054
|View full text |Cite
|
Sign up to set email alerts
|

Nationally and regionally representative analysis of 1.65 million children aged under 5 years using a child-based human development index: A multi-country cross-sectional study

Abstract: BackgroundEducation and health are both constituents of human capital that enable people to earn higher wages and enhance people's capabilities. Human capabilities may lead to fulfilling lives by enabling people to achieve a valuable combination of human functionings-i.e., what people are able to do or be as a result of their capabilities. A better understanding of how these different human capabilities are produced together could point to opportunities to help jointly reduce the wide disparities in health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…A recent review identified several promising interventions to remove barriers to girls’ school participation and learning in low- and middle-income countries, including lack of water and sanitation [ 22 ]. In terms of nutritional environment, school-based food assistance could provide students to have at least one proper meal a day, further improving both health and education outcomes jointly [ 23 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review identified several promising interventions to remove barriers to girls’ school participation and learning in low- and middle-income countries, including lack of water and sanitation [ 22 ]. In terms of nutritional environment, school-based food assistance could provide students to have at least one proper meal a day, further improving both health and education outcomes jointly [ 23 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously investigated the relationship between U5MR and various potential risk factors. Malnutrition, lifestyle, healthcare, and various socioeconomic factors have been identified as crucial determinants of U5MR ( Van Malderen et al, 2019 , Davenport et al, 2017 , De Neve et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it does not address the effects of war nor of ongoing ethnic discrimination in various populations regarding health to any great extent. However, we hope that the reader will be encouraged to seek out further writing in the area, which incorporates socioeconomic, political, cultural and behavioural modelling into healthcare, and which may bring greater enlightenment albeit no greater resolution to these questions [ 6 8 ].…”
mentioning
confidence: 99%